2021
DOI: 10.1097/sap.0000000000003025
|View full text |Cite
|
Sign up to set email alerts
|

The Declining Number of Finger Replantations in Germany

Abstract: Introduction: Data from the United States have shown that finger replantation numbers have declined significantly in recent years. It is unclear whether this is due to a decrease in amputation injuries or other reasons. Materials & Methods: Since 2005, all German hospitals have been required to produce structured quality reports. Based on these reports, we analyzed finger and hand replantation development and the incidence of amputation injuries between 2006 and 2018. Results: Replantations decreased by 30%, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Authors from Munich (Germany) aimed to review the German data to determine the rate of finger replantations and establish how and why this has changed over time. 6 They used a nationwide hospital database, which had been established to provide accurate data on workload to comply with German federal laws.…”
Section: The Declining Number Of Finger Replantations In Germanymentioning
confidence: 99%
See 1 more Smart Citation
“…Authors from Munich (Germany) aimed to review the German data to determine the rate of finger replantations and establish how and why this has changed over time. 6 They used a nationwide hospital database, which had been established to provide accurate data on workload to comply with German federal laws.…”
Section: The Declining Number Of Finger Replantations In Germanymentioning
confidence: 99%
“…Authors from Munich (Germany) aimed to review the German data to determine the rate of finger replantations and establish how and why this has changed over time. 6 They used a nationwide hospital database, which had been established to provide accurate data on workload to comply with German federal laws. Quality reports from an average of 2,000 hospitals are reported each year and were initially produced every two years, but have been produced annually since 2012.…”
Section: The Declining Number Of Finger Replantations In Germanymentioning
confidence: 99%
“…Traumatic digit amputation predominantly affects young working-age male individuals, with an increasing number of replantation procedures observed in Asian countries 4 6 . In contrast, the United States and Germany have seen a decline in the replantation rates owing to a refinement of indications, fewer patients with amputations, and declining reimbursement 6 8 . A difference in success rates was reported between facilities where many surgeries were performed and those in which a small number of surgeries were performed.…”
Section: Introductionmentioning
confidence: 99%
“…A difference in success rates was reported between facilities where many surgeries were performed and those in which a small number of surgeries were performed. If the number of surgeries continues to decline, the concern is that the technique of replantation will become more dispersed, and the success rate of surgeries will decline 8 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Decreases in replantation procedures have been documented in the US, and these findings have been associated with a spiral of decreased reimbursement, decreased availability of services, and decreased opportunities for training experience 9,10 . In Germany, Kükrek et al 11 reported a 30% decrease in replantation procedures over the period from 2006 to 2015, whereas amputations increased slightly over the same period. They also found that the number of centers performing at least 10 replantations a year fell by 40%, whereas most residents participated in fewer than 1 replantation case per year of training.…”
mentioning
confidence: 99%